Investigation of career indecision among Malaysian undergraduate students - Khasmohammadi, Mahdi; Mohd Noah, Sidek; Ehsaei, Sara Ghazizadeh (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The present study aimed to examine career indecision among Malaysian undergraduate students. The sample size of the study was 534 students aged from 18 to 24 which were chosen by a multi-stage cluster sampling method. For data collection Career Decision Scale (CDS) was utilized. The findings revealed that 74% of undergraduate students reported low to high career indecision, and only about 26% were decided about their future career. Furthermore, Male students scored lower in career indecision compared to females. Moreover, freshman students reported the highest level of career indecision in this study.